PEMETAAN SEBARAN IKAN TONGKOL (Euthynnus sp.) DENGAN DATA KLOROFIL-α CITRA MODIS PADA ALAT TANGKAP PAYANG (Danish-seine) DI PERAIRAN TELUK PALABUHANRATU, SUKABUMI, JAWA BARAT - Mujib, Zaki; Boesono, Herry; Purnamafitri, Aristi Dian (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2013)
Palabuhanratu waters is the center of important economic fisheries commodity like tinker mackerel (Euthynnus sp.). Statistic datas of PPNP (2011) showed that production value of fishery in Palabuhanratu was decreased 3% from a year before, that is have an impact to economy condition of Palabuhanratu. Payang (Danish-seine) as a one of pelagic fishing gear in Palabuhanratu have an imbalance condition between supplies and income. Tinker mackerel production decreased in 2011 resulted in the economic condition of fishermen Palabuhanratu decreased. As one of the predictors of the presence of fish, chlorophyll-a can be used in the determination of the study the fishing ground through remote sensing technology. The purpose of the studies are to analyze the factors that influence the distribution of tinker mackerel (Euthynnus sp.), analyze the relation of chlorophyll-a and the value of the catch, and create a map of potential Palabuhanratu tinker mackerel in the Palabuhanratu waters. The research method used was descriptive with the case study and data collection by purposive sampling. Chlorophyll-a values in March - April 2012 ranged from 0,70 mg / l – 2,585 mg / l, with an average value of 0,475 mg / l. The amount of catches reach 695 kg in March and April of 426,24 kg. The results of measurements of field data has showed that average of salinity, SPL, DO, current, and depth respectively: 33 ppt, 30,9° C, 6,28 mg / l, 0,108 m / s, and 288,67 m. The results of the regression test showed that current was the significant variable with a value of p=0,02 (p <0,05) and r = 0.690 (indicating a strong correlation). The results showed that correlation pattern between water quality parameters, chlorophyll-a, and the catch of mackerels (Euthynnus sp.). Based on field data and MODIS image overlay, potential fishing areas in March - April 2012 include: Cimandiri, Tanjung Kembar, Gedogan, Ujung Karangbentang, Ujung Sodongprapat, and the Gulf Amuran.